Techno-Economic Assessment and Optimization of a Standalone System in Sebira Island, Indonesia - Farah, Laili; Akhmad, Yus Rusdian; Saryadi, Rezky Mahardika; Mardha, Amil; Mudjiono, Mudjiomo; Nuryanti, Nuryanti; Anzhar, Kurnia; Handayani, Airine Hijrah (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
Nuclear power is known as a baseload generator in central power networks, but its implementation is too large-scale for microgrid applications. Nuclear power as a source of electricity is considered for microgrid applications due to its ability to produce emission-free energy. This research discusses the techno-economic analysis and optimization of a hybrid energy system design on Sebira Island, Indonesia, using a multi-year model in HOMER Pro software. Two scenarios were created: diesel-PV-battery and the second scenario, nuclear-PV-battery, with the baseline system being a diesel generator (DG) only. The research results show that with the optimal use of the nuclear-PV-battery system, the levelized cost of electricity (COE) is 0.128. This value is lower compared to the first scenario with a COE of 0.6577. The CO2 emissions generated in the optimal nuclear-PV-battery system are zero, making this system far more viable than other hybrid system schemes.